How larch becam a skwirt and why? - Szcześniak, Krystyna (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The article is an attempt to solve the genesis of the Lemko word skwirt (present in the name of the village of Skwirtne in Low Beskids). Based on the available written sources (from Slovak, Ukrainian and Polish areas, Polish, Ukrainian and Belarusian lexicons, as well as correspondence with famous botanicts, the author tries to explain not so much the ethymology of the lexeme (which is know), but the reasons for a specific intersection on a specific area (Lemko region) of the names of the trees: spruce and larch.